Religion in development: rewriting the secular script - Deneulin, Séverine (Zed, 2009)
Development practise is full of examples of the importance of religion in the lives of people in developing countries. However, religion has largely remained unexplored in development studies. This timely new book aims to fill that gap. The authors expertly review how religion has been treated in the evolution of development thought, how it has been conceptualised in the social sciences, and highlights the major deficiencies of the assumption of secularism. The book argues that development theory and practice needs to rewrite its dominant script regarding its treatment of religion, a script which has so far been heavily inscribed in the secular tradition. It puts forward an understanding of religions as traditions: that religions rest on central thesis and teachings which never cease to be re-interpreted in the light of the social, political and historical context. In addition to providing a conceptual framework for analysing the role of religion in development, the book provides numerous empirical examples drawn from the Christian and Islamic religious traditions. This comprehensive new guide to this key issue is essential for students, development thinkers and practitioners who wish to understand better the role taht religion plays in development processes and outcomes.